Mechanical Properties and Acoustic Emission Characteristics of Thawing Frozen Sandstone - Gengshe Yang; Bo Liang; Hui Liu; Yanjun Shen; Hailiang Jia (Advances in Materials Science and Engineering)
After the construction of a frozen shaft wall is completed, it undergoes a long thawing process. Damage accumulation under load may result in the rupture of the frozen wall and cause engineering accidents. The change in the mechanical properties of the frozen rock during the thawing process is crucial to the stability of the frozen wall. In this study, we selected Cretaceous saturated sandstone as the research object and performed uniaxial compression tests on the frozen sandstone to analyze its mechanical properties during the thawing process. In addition, acoustic emission technology was used to analyze the damage and failure characteristics of the rock. The main findings of the study are as follows: (1) the results of the uniaxial compression tests revealed that the thawing of frozen sandstone comprises five stages. The closure stress, crack initiation stress, expansion strength, and peak strength were obtained from the volumetric stress-strain curve. These four stress values act as the dividing points of the five stages. (2) The initiation stress of frozen sandstone at different temperatures accounts for approximately 50% of the peak strength. The strength value is low, the deformation is large, and it exhibits an obvious strain-softening phenomenon. (3) As the temperature increases, the closure level of the saturated sandstone gradually increases, and the crack initiation and expansion levels gradually decrease. (4) Based on the four characteristic stresses of the thawing process of frozen sandstone, the acoustic emission signal can be divided into a quiet period, an increasing period, a frequent period, a sharp increase period, and a decline period. (5) A frozen sandstone damage model was established based on the D-P failure criterion. The efficacy of the model was evaluated against the test data and was found to be reasonably accurate. This paper uses acoustic emission technology to simultaneously monitor the melting process of frozen rocks and reveal the relationship between intensity and temperature. The results provide theoretical and technical support for evaluating the mechanical damage induced by thawing of a frozen shaft wall.